Penentuan Portofolio Saham Optimal Menggunakan Metode Markowitz Sebagai Dasar Keputusan Investasi - Nisardi, Muhammad Rifki; Husain, Hartina; Kusnaeni, Kusnaeni; Resky, Aprizal (UIN Walisongo Semarang, 2024)
A stock portfolio is a combination of two or more securities invested over a specific period and under certain conditions. This study analyzes the combination of stocks that can be formed into an optimal portfolio using the Markowitz method. The Markowitz method is employed to maximize returns and minimize the risks associated with a portfolio. This method uses a mathematical formulation that allows for adjustments based on risk tolerance levels and expected returns to achieve an optimal portfolio. The data used in this study comprises the monthly closing prices of stocks from five selected companies, namely ICBP, BBCA, TLKM, BBNI, and INCO, for the period from June 2019 to December 2022. The findings indicate a recommended portfolio with the lowest risk, known as the Minimum Variance Portfolio (MVP). The MVP comprises the following proportions: ICBP 36.10%, BBCA 36.28%, TLKM 17.84%, INCO 8.39%, and BBNI 1.39%. This combination of stock proportions yields an expected return of 8.58% and a portfolio risk of 21.52%.Keywords: Markowitz method, Minimum Variance Portfolio, Portfolio Optimization.